Tizanidine-induced acute severe cystitis in a female taking famotidine - Poudel RR; Kafle NK (Dove Medical Press, 2015)
Resham Raj Poudel,1 Nisha Kusum Kafle2 1Department of Medicine, Om Saibaba Memorial Hospital, Kathmandu, Nepal; 2Department of Public Health, Institute of Medicine, Kathmandu, Nepal Abstract: Cystitis is a possible adverse drug reaction associated with the use of tizanidine. Such cases have been rarely reported in literature because of the difficulty in establishing the causality. However, from a pharmacovigilance point of view, it is better to report such cases of a possible association between a drug’s use and potential adverse drug reactions. We report a case of a 26-year-old Asian female on famotidine who presented with acute severe urinary burning after taking tizanidine. Keywords: adverse drug reaction, cystitis, famotidine, tizanidine